2011
DOI: 10.3109/02770903.2011.570406
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Behaviors and Beliefs in Urban Adolescents with Asthma

Abstract: Many urban adolescents used and would consider using CAM, specifically relaxation and prayer, for asthma symptom management. African-Americans, older adolescents, and those with more frequent symptoms were more likely to use and/or consider using CAM. Providers caring for urban adolescents with asthma should discuss CAM with patients, particularly those identified as likely to use CAM. Future studies should examine relationships between CAM use and health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
4
17
0
1
Order By: Relevance
“…Consistent with prior evidence, teens with better control regarded symptoms as more serious, responded sooner, and used fewer non-pharmacologic symptom-management strategies [3740]. Conversely, higher thresholds for treatment corresponded with greater symptom tolerance, delayed treatment patterns, and poorer control.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with prior evidence, teens with better control regarded symptoms as more serious, responded sooner, and used fewer non-pharmacologic symptom-management strategies [3740]. Conversely, higher thresholds for treatment corresponded with greater symptom tolerance, delayed treatment patterns, and poorer control.…”
Section: Discussionsupporting
confidence: 60%
“…Most the young adult participants 69.1% showed that use unconventional medicine in their life. Similar to previous studies [12,13] indicted that 71% and 80% of young adult using UM. In our study indicated that Quran/Roqua/pray, herbal medicine, honey therapy and sports therapy are common type of UM used by the young adults which similar to previous study include young adults and adults in Qassim Province [10] .…”
Section: Discussionsupporting
confidence: 74%
“…This study similar to previous studies that young adults can be affected by people [10,19] . The most common reason of using UM is treating illness which similar to other studies [10,12,13,19] . In this study showed similar previous studies [20] the young adult showed positive attitude about UM.…”
Section: Discussionsupporting
confidence: 50%
“…45 Based on clinical and populationspecific studies, adolescents most commonly use biologically based dietary approaches (both avoiding dietary triggers and taking dietary supplements) and mind-body practices, many of which can be implemented at costs lower than CAM modalities requiring professional assistance. [46][47][48][49] The efficacy of acupuncture, thermal biofeedback, and hypnosis for children with HA has been documented. 50 However, little is known about the extent of the use of these types of CAM therapies among youth experiencing HA.…”
Section: Resultsmentioning
confidence: 99%